Potential for Treatment of Neurodegenerative Diseases with Natural Products or Synthetic Compounds that Stabilize Microtubules - Miller, John H.; Das, Viswanath (Current Pharmaceutical Design, 2020)
No effective therapeutics to treat neurodegenerative diseases exist, despite significant attempts to find drugs that can reduce or rescue the debilitating symptoms of tauopathies such as Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, amyotrophic lateral sclerosis, or Pick’s disease. A number of in vitro and in vivo models exist for studying neurodegenerative diseases, including cell models employing induced-pluripotent stem cells, cerebral organoids, and animal models of disease. Recent research has focused on microtubulestabilizing agents, either natural products or synthetic compounds that can prevent the axonal destruction caused by tau protein pathologies. Although promising results have come from animal model studies using brainpenetrant natural product microtubule-stabilizing agents, such as paclitaxel analogs that can access the brain, epothilones B and D, and other synthetic compounds such as davunetide or the triazolopyrimidines, early clinical trials in humans have been disappointing. This review aims to summarize the research that has been carried out in this area and discuss the potential for the future development of an effective microtubule stabilizing drug to treat neurodegenerative disease.
Keywords: triazolopyrimidine